Hospital variation in downstream secondary preventive medication uptake: implications for quality and outcomes. (25th November 2020) - Jug, B; Dosenovic Bonca, P; Fras, Z
Abstract: Background: Adherence to guideline recommended therapy improves outcomes in patients with myocardial infarction. We sought to appraise between-hospital variation in downstream adherence to secondary preventive medication and hypothesised that discharge from high-adherence hospitals was associated with improved long-term outcomes. Methods: We included 7, 624 patients hospitalised because of myocardial infarction in 14 hospitals between 2015 and 2017 in Slovenia (nation-wide sample). Using indirect identifiers, we linked routinely collected data on patients from the i) Hospital Discharge Statistics Database, ii) the National Mortality Registry and iii) the Medication Reimbursement Database. We used random intercept logistic regression modelling for prediction of secondary prevention medication uptake 30 to 90 days after discharge, adjusting for case-mix, hospital size and percutaneous coronary intervention (PCI) availability. We classified hospitals into high- and low adherence (i.e., above and below the national median adjusted odds) and assessed the association between hospital performance, and death or re-infarction with multivariate Cox proportional hazards modelling. Results: Secondary preventive medication uptake ranged from 30.7% to 87.3% in high- and low-performing hospitals, respectively. Discharge from high-adherence hospitals were associated with significantly lower all-cause mortality and re-infarction rates (hazard ratio 0.82; 95% confidence interval 0.69–0.98) when compared to hospitals with secondary preventive medication uptake below the national median, after adjusting for case-mix and hospital characteristics. Conclusions: Downstream secondary preventive medication uptake vary across hospitals. Although case-mix and hospital characteristics explain some of the variation, discharge from a hospital with good downstream secondary preventive medication uptake is associated with lower risk of death or re-infarction. Funding Acknowledgement: Type of funding source: None